An assessment of the World Rugby law application guidelines for the breakdown on sanctioning and player adherence - Mitchell, S. L.; Tierney, G. J. (International Journal of Sports Science & Coaching, 2023)
World Rugby`s law application guideline for the breakdown was developed to make the breakdown safer, fairer, and simpler to understand. The aim of this study was to use video analysis to assess the impact of these guidelines by comparing player adherence from the 2019 Rugby World Cup (pre-guidelines) to the 2020 Autumn Nations Cup (post-guidelines) as well as the rate of sanctioning by match officials. Contested breakdowns (n = 1444) were individually analysed by coding any infringement that occurred as well as the sanctioning outcome. The chi-square and probability (p) values were calculated to compare proportions before (pre) and after (post) the law application guidelines. No change in the rate of infringements was observed (p = 0.207), though the rate of infringements penalised increased (p = 0.001). Reductions in the rate of infringements of two of the five offences targeted by the guidelines were observed; "offside" (p = 0.008) and "remains on feet" (p <0.001). All dangerous play infringements reduced; "charged in" (p <0.001), "contact above shoulder" (p <0.001), "intentional collapse" (p = 0.023). There are early indications that the guidelines have had a marginal influence on overall player adherence to the breakdown rules but a considerable positive influence on adhering to the rules surrounding dangerous play.